(untitled) (Journal of Economic Research & Business Administration, 2026)
The article is devoted to the study of the impact of the development of artificial intelligence (AI) on labor productivity and economic growth in countries with different levels of economic development. The object of the study is the processes of economic growth in the context of the digital transformation of the global economy. The purpose of the study is to identify and quantify the relationship between the development of AI, the dynamics of labor productivity, and GDP per capita based on a cross-country analysis for the period 2015-2024.The study uses a panel econometric analysis of data from six countries (the United States, China, Germany, South Korea, India, and Kazakhstan) for the period 2015–2024, including correlation analysis and regression modeling. The results show a statistically significant positive relationship between AI investment and the labor productivity index (coefficient of 0.62; p < 0.01). The correlation analysis also revealed a high degree of linear relationship between the studied indicators in all the sample countries. The analysis showed that the magnitude of the effect varies depending on the level of economic development and the amount of technological capital. The scientific novelty of the study lies in the comprehensive cross-country comparison of AI investments, patent activity, and labor productivity dynamics in a single cross-country model, which allowed us to identify the heterogeneity of technological effects in developed and emerging economies. The results confirm the importance of AI investments as a factor in increasing production efficiency, but the interpretation of this relationship requires consideration of possible endogenous effects and structural features of national economies.The practical significance of this work lies in substantiating the need for priority development of digital infrastructure and human capital as key factors in sustainable economic growth. The research results can also be used in the development of strategic planning, regulation of AI implementation, forecasting changes in the industry structure, and increasing competitiveness in various sectors of the economy. Keywords: artificial intelligence (AI), labor productivity, economic growth, innovative technologies, correlation analysis.